Transcutaneous Electrical Acupoint Stimulation in Early Life Changes Synaptic Plasticity and Improves Symptoms in a Valproic Acid-Induced Rat Model of Autism - Xiaoxi Wang; Rui Ding; Yayue Song; Juan Wang; Chen Zhang; Songping Han; Jisheng Han; Rong Zhang (Neural Plasticity)
Autism spectrum disorder (ASD) is a developmental disorder characterized by social behavior deficit in childhood without satisfactory medical intervention. Transcutaneous electrical acupoint stimulation (TEAS) is a noninvasive technique derived from acupuncture and has been shown to have similar therapeutic effects in many diseases. Valproic acid- (VPA-) induced ASD is a known model of ASD in rats. The therapeutic efficacy of TEAS was evaluated in the VPA model of ASD in the present study. The offspring of a VPA-treated rat received TEAS in the early life stage followed by a series of examinations conducted in their adolescence. The results show that following TEAS treatment in early life, the social and cognitive ability in adolescence of the offspring of a VPA rat were significantly improved. In addition, the abnormal pain threshold was significantly corrected. Additional studies demonstrated that the dendritic spine density of the primary sensory cortex was decreased with Golgi staining. Results of the transcriptomic study showed that expression of some transcription factors such as the neurotrophic factor were downregulated in the hypothalamus of the VPA model of ASD. The reduced gene expression was reversed following TEAS. These results suggest that TEAS in the early life stage may mitigate disorders of social and recognition ability and normalize the pain threshold of the ASD rat model. The mechanism involved may be related to improvement of synaptic plasticity.